2011
DOI: 10.1097/nnr.0b013e3182002e46
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial Testing Efficacy of a Nurse-Coached Intervention in Arthroscopy Patients

Abstract: The findings suggest that telephone calls from nurses during the immediate postoperative period resulted in improved patient outcomes, namely, less symptom distress and better physical and mental health states. In future research, the study sample should be expanded to older and more diverse patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…[6][7][8] However, successful day surgery requires not only surgery, but also successful post-treatment, with patient education having a particularly important role in this. Effective and clear patient education seeks to improve patient knowledge and operational performance, [9][10][11][12][13] optimize patient recovery, shorten hospital stays for patients, improve satisfaction with health care, reduce the risks associated with surgery, [14][15][16][17] as well as help to reduce the pressures on societal health services. 18 Day surgery is an innovative treatment whose popularity and demand is growing all the time.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] However, successful day surgery requires not only surgery, but also successful post-treatment, with patient education having a particularly important role in this. Effective and clear patient education seeks to improve patient knowledge and operational performance, [9][10][11][12][13] optimize patient recovery, shorten hospital stays for patients, improve satisfaction with health care, reduce the risks associated with surgery, [14][15][16][17] as well as help to reduce the pressures on societal health services. 18 Day surgery is an innovative treatment whose popularity and demand is growing all the time.…”
Section: Introductionmentioning
confidence: 99%
“…61 Caregivers not only rated the program as helpful but identified new skills they had gained, likely based on their improved self-efficacy for home HF care. 62,63 These findings reflect the feedback loops in the coaching framework, illustrated by the curved arrows in Figure 1. Specifically, the narrative data from both nurses and caregivers indicated that coaching program improved aspects of HF home self-management skills (intermediate outcomes).…”
Section: Discussionmentioning
confidence: 52%
“…25,26 Coaching professionals engage caregivers in specific strategies based on evidence-based national clinical guidelines. The use of nurse coaching strategies (left column) are designed to improve caregiver HF home management skills which can then improve patient and caregiver outcomes 27,28 The coaching strategies the nurse uses are the posited behavioral self-efficacy mechanisms 29,30 that then increase the intermediate caregiver outcomes (center column) such as knowledge, confidence, preparedness. The combined intermediate outcomes result in the long-term outcomes (right column) such as reduction in caregiving burden improvement in both patient and caregiver health.…”
Section: Purposementioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19] Nurse coaches hold positions in governmental regulatory agencies. In addition to their presence in all these areas, these professionals are caring for the full array of patients in oncology, 20-23 cardiology, pediatrics, etc., in acute-care settings, primary care, 24,25 home care, hospice settings, hospitals, 26,27 clinics, and long-term and rehabilitation centers. 28…”
Section: Why a Nurse Coach?mentioning
confidence: 99%